ADVERTISING SUNK COSTS AND CREDIBLE SPATIAL PREEMPTION - Thomas, Louis A. (Strategic Management Journal, 1996)
Large sunk investments in advertising allow managers to credibly preempt potential entrants by introducing new products prior to anticipated increases in market growth. Previous investment in advertising can lower a firm's cost to introduce new products allowing it to credibly preempt potential entrants. Entrants may not have enough residual share to find it profitable to enter later, and incumbents find it profitable to keep new products in the market even if entrants choose to enter. I present empirical evidence from the RTE cereal industry.